2016
DOI: 10.1080/2162402x.2016.1250050
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ewing sarcoma with activated and GD2-specific chimeric antigen receptor-engineered human NK cells induces upregulation of immune-inhibitory HLA-G

Abstract: Activated and expanded natural killer (NK) cells have substantial cytotoxicity against many tumor cells, but their efficacy to eliminate solid cancers is limited. Here, we used chimeric antigen receptors (CARs) to enhance the activity of NK cells against Ewing sarcomas (EwS) in a tumor antigen-specific manner. Expression of CARs directed against the ganglioside antigen G in activated NK cells increased their responses to G+ allogeneic EwS cells and overcame resistance of individual cell lines to NK cell lysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 49 publications
2
81
1
Order By: Relevance
“…In preclinical studies, it could be shown that disialoganglioside- (GD 2 ; expressed on tumours of neuroectodermal origin [68]) positive Ewing sarcoma (ES) cells could be used for the engineering of a second- and third-generation anti-GD 2 -CAR. This led to an improvement of the NK cell-driven cytotoxicity against several cancer cell lines in vitro and resulted in effective counteraction against ES tumour resistance [69, 70]. However, adoptive transfer of anti-GD 2 -CAR-NK cells in GD 2 -expressing ES xenograft models could not confirm previous in vitro experiments [70].…”
Section: Effectiveness Of Car-engineered Primary Nk Cells Against Solcontrasting
confidence: 39%
See 2 more Smart Citations
“…In preclinical studies, it could be shown that disialoganglioside- (GD 2 ; expressed on tumours of neuroectodermal origin [68]) positive Ewing sarcoma (ES) cells could be used for the engineering of a second- and third-generation anti-GD 2 -CAR. This led to an improvement of the NK cell-driven cytotoxicity against several cancer cell lines in vitro and resulted in effective counteraction against ES tumour resistance [69, 70]. However, adoptive transfer of anti-GD 2 -CAR-NK cells in GD 2 -expressing ES xenograft models could not confirm previous in vitro experiments [70].…”
Section: Effectiveness Of Car-engineered Primary Nk Cells Against Solcontrasting
confidence: 39%
“…Furthermore, the diminished anti-tumour response of those CAR-modified NK cells was connected to increased expression levels of immunosuppressive human leukocyte antigen G (HLA-G) on ES cells, thereby mediating tumour immune escape [71]. The authors concluded that HLA-G represents a potential checkpoint, which would have to be inhibited before initiating therapies based on CAR-NK cells [70]. …”
Section: Effectiveness Of Car-engineered Primary Nk Cells Against Solmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, NK cells exert cytotoxicity against a number of hematologic malignancies, including acute myeloid leukemia (AML), 26-28 ALL, 29-33 multiple myeloma (MM), [34][35][36][37] as well as many solid tumors including neuroblastoma, ovarian, colon, renal cell, and gastric carcinomas. 33,[38][39][40][41][42] However, many tumors develop evasion strategies to circumvent killing by autologous NK cells. 27,31 For example, some leukemia and lymphoma cells maintain high surface expression of HLA molecules, making them invisible to NK attack, 31,32 or may lack ligands that signal through activating NK cell receptors.…”
Section: Adoptive Transfer Of Nk Cells To Target Tumorsmentioning
confidence: 99%
“…Overall, standardized measurements for the production and quality control of NK cells are lacking, possibly causing substantial variations in therapeutic outcomes. [34]. CAR-NK cells targeting well-known targets, such as CD19, CD20, SLAMP7, and EpCAM, have been tested in vivo with in-mouse models or in vitro.…”
Section: Adoptive Cell Transfer (Act)mentioning
confidence: 99%